Analysis Of Birth Certificate Issuance Services For Children Resulting From Siri Marriages In The Population And Civil Registration Office Of Central Bengkulu District - Bella Sagita; Nour Farozi Agus; Azuwandri (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This research focuses on the issue of issuing birth certificates to children from siri marriages in Bengkulu Tengah Regency. The purpose of this research is to understand the process of birth certificate issuance services for children from siri marriage, identify the obstacles that arise in the process, and evaluate the efforts made by the Population and Civil Registration Office of Bengkulu Tengah Regency in improving birth certificate issuance services for children from siri marriage. This research uses descriptive research methods, qualitative descriptive methods are research methods based on the philosophy of postpositivism used to research on natural object conditions where the researcher is a research instrument and the results of the writing are in the form of words or statements that match the actual situation. The data collection source describes the analysis method using reduction, presentation, and conclusion.The service procedures for making deeds have navigated the procedures and regulations that apply. 2. People who do not have a marriage certificate, show that the service of issuing birth certificates for children from siri marriage shows that it is good and gets satisfaction in the community and gets the result that the making of the late certificate is the fault of the community itself because it does not know the information and lack of knowledge by the community. Evidenced in the results of interv